Hubungan Faktor Sosiodemografi dengan Perilaku Swamedikasi Obat Analgesik pada Masyarakat Kota Malang - Yusuf, Muhammad Faishal; Sugihantoro, Hajar; Hakim, Abdul; Maulina, Novia; Ummah, Syifaul Khoiro (Jurnal Ilmiah Medicamento, 2025)
The prevalence of self-medication among the population of Malang City reached 64.35% in 2022. This figure indicates a considerable potential risk, particularly related to inappropriate medication practices. Analgesics are among the most used drugs for pain relief through self-medication. Improper use of analgesics may lead to adverse effects, including gastrointestinal disturbances, hypersensitivity reactions, and damage to the kidneys and liver. This study aims to examine self-medication behavior involving analgesics and to analyze the relationship between respondents’ sociodemographic factors and such behavior. The research employed quantitative analytic observational design with a cross-sectional approach and survey method. Sampling was conducted using a non-probability sampling technique, involving 100 respondents who met the inclusion and exclusion criteria. Data analysis was performed using non-parametric statistical tests, namely the Chi-Square test for gender, occupation, and residence variables, and the Spearman Rank test for age, income, and education level. The results showed that the self-medication behavior with analgesics among the people of Malang City was categorized as “moderate,” with a prevalence of 72%. Statistical analysis revealed significant associations between age, income, education level, and residential area with analgesic self-medication practices. Conversely, gender and occupation did not show statistically significant relationships. These findings provide a foundation for developing targeted educational strategies and public health policies to promote safer and more rational self-medication practices.